2015
DOI: 10.17235/reed.2015.3868/2015
|View full text |Cite
|
Sign up to set email alerts
|

Neomycin and bacitracin reduce the intestinal permeability in mice and increase the expression of some tight-junction proteins

Abstract: Background: Tight-junction (TJ) proteins regulate paracellular permeability. Gut permeability can be modulated by commensal microbiota. Manipulation of the gut microbiota with antibiotics like bacitracin and neomycin turned out to be useful for the treatment of diarrhoea induced by Clostridium difficile or chemotherapy drugs.Aim: To evaluate the effects of the microbiota depletion evoked by the oral administration of neomycin and bacitracin on the intestinal permeability and expression of TJ proteins in mice.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…The results showed that feeding oxidized oils down regulated occludin and claudin-1 mRNA expression in the ileum and suggest that the regulation of occludin and claudin-1 expression by oxidized oils may be increase intestinal permeability, leading intestinal barrier dysfunction. These results were in agreement with other reports on animals suffering oxidative stress (Casselbrant et al, 2015, Nevado et al, 2015, Suzuki & Hara, 2010. According to John et al (2011), excessive levels of reactive oxygen species in intestines may contribute to barrier dysfunction, as indicated by a disruption of composition of the tight junctions.…”
Section: Effect Of Oxidized Soybean Oils On Oxidative Status and Intesupporting
confidence: 93%
“…The results showed that feeding oxidized oils down regulated occludin and claudin-1 mRNA expression in the ileum and suggest that the regulation of occludin and claudin-1 expression by oxidized oils may be increase intestinal permeability, leading intestinal barrier dysfunction. These results were in agreement with other reports on animals suffering oxidative stress (Casselbrant et al, 2015, Nevado et al, 2015, Suzuki & Hara, 2010. According to John et al (2011), excessive levels of reactive oxygen species in intestines may contribute to barrier dysfunction, as indicated by a disruption of composition of the tight junctions.…”
Section: Effect Of Oxidized Soybean Oils On Oxidative Status and Intesupporting
confidence: 93%
“…Taken together, our results suggest that the AIM2 receptor is required for the maintenance of the intestinal barrier through the regulation of tight-junction proteins and the RegIIIγ expression by intestinal epithelium during T1D. Considering that tight-junction proteins are involved in the regulation of intestinal permeability [40][41][42][43], we next evaluated whether AIM2 deficiency alters the gene expression of tight-junction proteins, such as zonnulin-1 (ZO-1), claudin-2, and occludin, after the STZ injections. Interestingly, the gene expression of ZO-1, claudin-2 and occludin was significantly increased at 7 days after the STZ injections in the ileum of the WT mice.…”
Section: Aim2 Receptor Controls Intestinal Permeability Through the Rmentioning
confidence: 53%
“…Recent studies have shown that antibiotic treatment can alter the regulation of the intestinal mucosal barrier (54)(55)(56) and downregulate the expression of RegIII␥ (43), which in turn could lead to translocation of commensals across the intestinal epithelium. We have found that systemic ceftriaxone administration was associated with significant reduction in the transcriptional expression of RegIII␥; however, our studies in RegIII␥ knockout mice suggest that it is not essential in the intestinal containment or extraintestinal dynamics of enterococci.…”
Section: Discussionmentioning
confidence: 99%